1985
DOI: 10.1111/j.1095-8649.1985.tb04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Threadfin shad, Dorosoma petenense Günther, mortality: causes and ecological implications in a South‐eastern United States reservoir

Abstract: Cold stress was identified as an important factor influencing both reservoir-wide mortality and impingement of threadfin shad, Dorosorna perenense, during the period October 1976 to April 1977 in Watts Bar Reservoir, Tennessee. Relative numbers and size frequency of impinged threadfin shad were similar to the relative numbers and size frequency of shad preyed upon by sauger, Sfizosredion canadense, and skipjack herring, AIosa chrysochloris. This relationship implies that the factor mainly responsible for impin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These observations (and trawl catches) suggested that at low temperatures, sole are sluggish and do not exhibit the normal behaviour of burrowing during the day, making them more vulnerable to cod predation. Similarly, McLean et al (1985) suggested that the reduced schooling behaviour of threadfin shad Dorosoma petenense (Günther) below 12° C increases vulnerability to predation by sauger Stizostedion canadense (Smith) and skipjack herring Alosa chrysochloris (Rafinesque). As low temperatures increase the metabolic requirements of endothermic avian and mammalian predators, they may represent a substantial, but unevaluated, risk to some overwintering fishes (Winship et al , 2002).…”
Section: Predationmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations (and trawl catches) suggested that at low temperatures, sole are sluggish and do not exhibit the normal behaviour of burrowing during the day, making them more vulnerable to cod predation. Similarly, McLean et al (1985) suggested that the reduced schooling behaviour of threadfin shad Dorosoma petenense (Günther) below 12° C increases vulnerability to predation by sauger Stizostedion canadense (Smith) and skipjack herring Alosa chrysochloris (Rafinesque). As low temperatures increase the metabolic requirements of endothermic avian and mammalian predators, they may represent a substantial, but unevaluated, risk to some overwintering fishes (Winship et al , 2002).…”
Section: Predationmentioning
confidence: 99%
“…Increased predation pressure could be caused by changes in distribution associated with seasonal migration of the predator, prey or an alternative prey (Murawski, 1993;Cooney et al, 2001). Changes in behaviour and swimming performance at low temperatures may also result in increased vulnerability to predators (Woodhead, 1964a;McLean et al, 1985). In addition to enhanced field sampling to describe diets and distributions, this field would benefit from better characterization of behavioural responses of fish to low temperatures (Lemons and Crawshaw, 1985;Hurst & Duffy, 2005;Hurst, 2007).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Equilibrium loss and reflex impairment are often thought of as symptoms of chemical anaesthesia (Summerfelt & Smith, 1990) and also can occur following cold stress or other debilitating stressors such as toxicity (McKim et al ., 1987). Equilibrium loss in wild fish has obvious implications for failure to avoid predators ( e.g ., Danylchuk et al ., 2007) or impingement against hydroelectric facility structures (McLean et al ., 1985). Hassan et al .…”
Section: Cold Stress and The Generalized Stress Response In Fishmentioning
confidence: 99%